Amos : a commentary based on Amos in Codex Vaticanus - Glenny, W. Edward. (Septuagint Commentary Series., 2013)
In this commentary W. Edward Glenny provides a careful analysis of the Greek text and literary features of Amos based on its witness in the fourth century codex Vaticanus. The commentary begins with an introduction to Amos in Vaticanus, and it contains an uncorrected copy of Amos from Vaticanus with textual notes and a literal translation of that text. In keeping with the purpose of Brill's Septuagint Commentary Series Glenny seeks to interpret the Greek text of Amos as an artifact in its own right in order to determine how early Greek readers who were unfamiliar with the Hebrew would have understood it.